Beyond the business plan : 10 principles for new venture explorers - Bridge, Simon.
"A new way of approaching start-ups which encourages a more flexible plan that allows for uncertainty and change Business plans do not allow for the unexpected. Often written at the outset of a new business proposal, there is little room for change or learning from experience once the venture is underway. Beyond the Business Plan provides 10 new principles for starting a new venture that support and encourage the flexibility to face uncertainties. These principles provide an alternative tool for use instead of the traditional business plan as a start-up guide -- helping to build a venture appropriate for the circumstances instead of trying to construct a pre-conceived model.. This book does not dictate how to run a venture but provides the insight needed to explore what is possible, to overcome unforeseen obstacles, to adapt, grow, and change as necessary. This fresh approach teaches how to be responsive to uncertainty and provides a flexible approach that is needed for navigating in the changing world economy which cannot be mapped until it is experienced. "--